Equity in Global North–South research partnerships: interrogating UK funding models. Issue 1 (14th June 2022) - Flint, Adrian; Howard, Guy; Baidya, Manish; Wondim, Tadesse; Poudel, Moti; Nijhawan, Anisha; Mulugeta, Yohannes; Sharma, Subodh
Abstract : This article considers the degree to which achieving equity in Global North–South research partnerships is possible under current UK funding models. While there has been significant discussion with respect to the decolonisation of research, it will be argued that there is some distance between the language of equity articulated currently by UK funding bodies, and the realities of working as a project partner in the Global South. The article draws on the prior and ongoing experiences of a multidisciplinary team of researchers brought together by a UK-funded research project. In the interests of moving towards more equitable systems of knowledge production and dissemination, it explores the power asymmetries that can be inherent in Global North–South research partnerships, and the extent to which issues of coloniality continue to shape aspects of research agenda setting, project framing, impact, academic publishing and the division of labour within partnerships.